Central and peripheral characterisation of TLR7/8 and endocannabinoid signalling in multiple sclerosis - Hackett, Becky (Trinity College Dublin. School of Medicine. Discipline of Physiology, 2022)
Toll-like receptors (TLRs) are a class of pattern-recognition receptors (PRRs) involved in initiating an immune response to infection or endogenous damage. These receptors are expressed on cells of both the innate and adaptive immune system and recognise conserved pathogenic motifs of bacterial, fungal and viral origins, as well as endogenous danger signals. The activation of TLRs results in downstream activation of intermediate adaptor proteins which culminate in the expression of a variety of cytokines, chemokines and interferons (IFNs), as well as priming of a specific adaptive immune response. A wide body of literature indicates that TLRs have roles to play in the pathophysiology of several diseases. Indeed, many studies have implicated TLR signalling in the pathophysiology of multiple sclerosis (MS) and its animal model, experimental autoimmune encephalomyelitis (EAE). Endosomal TLRs (comprising TLR3, TLR7, TLR8 and TLR9) play a pivotal role in the recognition of viruses as well as clearing of viral infection. The epstein barr virus (EBV) has strong association with the risk of developing MS. Thus dysregulation of viral TLRs may prove key in the pathophysiology of MS. Indeed, our laboratory has previously identified key roles for both viral TLRs (TLR3) and bacterial TLRs (TLR4) in immune cells associated with MS. Thus, we sought to assess the potential functional role of TLR7 and TLR8, two closely-related endosomal TLRs, in the pathophysiology of MS, both centrally and peripherally. Both TLR7 and TLR8 signal through the myeloid differentiation primary response protein 88 (MyD88) adaptor, which has been shown to be instrumental in the development of EAE. Thus targeting TLR7/8 signalling may prove beneficial in MS, and offer insight on the role(s) of endosomal TLRs in MS pathogenesis. Phytocannabinoids (pCBs) are cannabinoid compounds isolated from the dioecious plant Cannabis L. sativa. The use of medicinal cannabis has spanned many centuries in the treatment of a plethora of ailments. Indeed, the pCB Δ9-tetrahydrocannabinol (THC), has been shown to exert neuroprotective and anti-inflammatory properties in the context of neurodegenerative disease. This is likely a result of its actions through the cannabinoid receptor 1 (CB1) that is present at high levels in the brain. THC however, has also been associated with euphoria and psychosis, and is responsible for the high associated with recreational cannabis use. Cannabidiol (CBD), another major pCB isolated from the cannabis plant, has shown no euphoric or psychotic symptoms, and furthermore can mitigate the psychoactive side effects associated with THC. CBD possesses neuroprotective, as well anti-inflammatory, propensity. Indeed, previous experiments in our laboratory have shown that pre-treatment of human macrophages with CBD can inhibit TLR3/4-dependent induction of inflammatory cytokines and chemokines. TLR4 classically signals via the MyD88 pathway, while TLR3 signals via the TIR-domain containing adapter-inducing interferon-β (TRIF)-dependent pathway, independent of MyD88. TLR4 can also signal via TRIF. Little evidence currently exists regarding the impact of CBD on MyD88-dependent endosomal TLR signalling, particularly in inflammatory diseases such as MS. Hence, a key goal of this study was to determine if endosomal TLR signalling via MyD88 is targeted by CBD. This project first set out to characterise TLR7 and TLR8 inflammatory signalling pathways in THP-1 macrophages. Data presented herein indicates that TLR7/8-induced inflammatory signalling pathways are operative in THP-1 macrophages, as indicated by induction of C-X-C motif chemokine ligand 10 (CXCL10) and tumor necrosis factor alpha (TNF-α). However, the TLR7/8 agonist CL075 failed to induce production of the type I IFN, IFN-, in THP-1 macrophages. Data presented herein also indicates that treatment of THP-1 macrophages with CL075 promoted an increase in the expression of TLR8 mRNA. Components of the endocannabinoid system (eCS) were also identified in THP-1 macrophages, and our findings indicate that TLR7/8 activation has the proclivity to alter the expression profile of components of the eCS in macrophages. CBD treatment did not impact TLR7/8-induced pro-inflammatory signalling, or impact on expression levels of the eCS, in macrophages. This suggests that CBD does not target inflammatory signalling via the endosomal MyD88-dependent TLR signalling pathway in THP-1 macrophages. In this study we also set out to determine if the expression profile of endosomal TLR7 and TLR8, in addition to components of the eCS, are altered in immune cells and brain tissue in MS. For primary immune cell analysis informed consent was obtained from each participant and the study received ethical approval from Beaumont Hospital Ethics and the Faculty of Health Sciences Research Ethics Committee, TCD. Post-mortem brain samples were provided by the UK MS Society Tissue Bank and were collected following informed consent by the donors via a prospective donor scheme according to Ethics committee approval. We characterised the expression profile of TLR7 and TLR8, and components of the eCS, including cannabinoid receptors (CB1/2), FAAH (responsible for hydrolysing anandamide) and MAGL (hydrolyses 2-AG), in peripheral blood mononuclear cells (PBMCs) isolated from healthy volunteers and people with MS, and in post-mortem human cortical brain samples from primary progressive MS, secondary progressive MS, and non-MS control cases. Our findings indicate that TLR7/8, and the eCS, are expressed in immune and CNS tissue, and provide evidence of alterations in TLR7/8 expression, and the eCS, in the cortex of MS cases. Overall, this study indicates a role for endosomal TLR7/8 in central pathophysiology of MS and this may impact signalling via the eCS. In addition, data presented in this project suggest that CBD does not impact classical MyD88-dependent signalling via TLR7/8. This may have implications in terms of the cellular effects of cannabinoid therapeutics in MS.
APPROVED